Field evaluation of a rapid, visually-read colloidal dye immunofiltration assay for Schistosoma japonicum for screening in areas of low transmission - Xiang Xiao; Tianping Wang; Hongzhuan Ye; Guangxiang Qiang; Haiming Wei; Zhigang Tian (The World Health Organization, 2005)
OBJECTIVE: To determine the validity of a recently developed rapid test - a colloidal dye immunofiltration assay (CDIFA) - used by health workers in field settings to identify villagers infected with Schistosoma japonicum. METHODS: Health workers in the field used CDIFA to test samples from 1553 villagers in two areas of low endemicity and an area where S. japonicum was not endemic in Anhui, China. All the samples were then tested in the laboratory by laboratory staff using a standard parasitological method (Kato-Katz), an indirect haemagglutination assay (IHA), and CDIFA. The results of CDIFA performed by health workers were compared with those obtained by Kato-Katz and IHA. FINDINGS: Concordance between the results of CDIFA performed in field settings and in the laboratory was high (kappa index, 0.95; 95% confidence interval, 0.93-0.97). When Kato-Katz was used as the reference test, the overall sensitivity and specificity of CDIFA were 98.5% and 83.6%, respectively in the two villages in areas of low endemicity, while the specificity was 99.8% in the non-endemic village. Compared with IHA, the overall specificity and sensitivity of CDIFA were greater than 99% and 96%, respectively. With the combination of Kato-Katz and IHA as the reference standard, CDIFA had a sensitivity of 95.8% and a specificity of 99.5%, and an accuracy of 98.6% in the two areas of low endemicity. CONCLUSION: CDIFA is a specific, sensitive, and reliable test that can be used for rapid screening for schistosomiasis by health workers in field settings.